Womens' agribusiness access index - Adedeji, Oluwaseun; Sudarkasa, Michael; Rowan-Campbell, Dorienne; Reynier, Aurélie (Technical Centre for Agricultural and Rural Cooperation, 2019)
This brief outlines why we need an index to measure and monitor women’s access to the services, markets, policies and other aspects constraining their ability to contribute to and benefit from opportunities in agriculture and agribusiness, especially in the developing world. This would allow policy-makers, women’s development advocates and development partners to better focus their efforts so they make agriculture work for women.